A Cross-Sectional Study on Factors Related to Status of Meconium Stained Liquor Labour Patients Attended at Tertiary Level Hospital in Dhaka, Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Meconium-stained liquor during labor is a common almost daily encountered problem.Objective: The purpose of the study was to find out factors related to meconium-stained liquor affecting during labor.Methodology: This is a cross-sectional, hospital-based observational study conducted in the Department of Obs & Gyne, Shaheed Suhrawardy Medical College Hospital, Dhaka. The cases with single, term pregnancy with cephalic presentation presented with meconium-stained liquor was selected. All the cases willingly participated in this study. Data collection and fetal assessment was conducted in the labor room. The meconium-stained liquor was clinically and completely in a structured questionnaire according to the events that happened pre and post-delivery including neonatal outcome data. Data was analyzed by computer using the SPSS program (Statistical Package of Social Sciences), version-22, and p value